Gen Z Teens Moral Degeneration In Entering the Modern Era Working World Phase - Ian Timothy Fairley; Linawati Neny Yunitasari ; Yustina Denik Risyanti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This journal consist of the brief explanation of a certain theory which I as the writer of it would like to explain and give a certain comment, criticism, readback, and thoughts about how this theory will proceed ahead in the future and its impacts toward positive and negative aspects for the subject that I will explain in this journal. For the theory that I myself chose for this journal would be the theory about “Moral Degeneration” towards the current new Zoomers teenager or Generation Z which are undergoing the process of joining the world of work life. The basic idea of which I am going to explain will be how this theory is brought up and how is it going on for companies and work field right now, hope that this journal would bring positive readback for the readers, thank u